Pengaruh Kecepatan Putar Terhadap Hasil Coran pada Metode Pengecoran Sentrifugal dalam Pembuatan Produk Pisau Pakan Ternak dengan Material Ni-Hard1 - Kusnowo, Roni; Hanaldi, Kus (Manutech : Jurnal Teknologi Manufaktur, 2019)
Animal feed knife is a tool that serves to cut and chop animal feed consisting of grass as the main ingredient with additives such as bran, herbs, centrate, cassava, tofu pulp and others. Therefore, as a cutting tool must have the properties of friction resistance, impact resistance, and have good sharpness, so that the material chosen is Ni-Hard 1. The use of centrifugal casting method was chosen because it has the advantage of being able to make castings with relatively thin thickness this is due to the influence of the centrifugal force on the distribution of metal liquids throughout the cavity in the mold. Case study in this study is the use of centrifugal casting methods as an alternative to gravity casting methods to overcome defects of misruns. This research was conducted to investigate the effect of speed on the formation of castings products. The method that was carried out began with a literature study on centrifugal casting, and continued by determining the material, the temperature of the cast is in the range 1250ºC - 1300ºC, and the type of mold. The next step is to do work drawings, pattern making, mold making, casting processes, fettling processes, and analysis. With variations in speed of 200 rpm, 300 rpm and 400 rpm, it can be seen the optimal speed for making this product. The results of this study obtained optimal speed at a speed of 300 rpm to make good quality of animal feed knife products.